1999
DOI: 10.1083/jcb.147.3.631
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Promotes Motility in Human Breast Cancer Cells Regardless of Their E-Cadherin Expression

Abstract: E-cadherin is a transmembrane glycoprotein that mediates calcium-dependent, homotypic cell–cell adhesion and plays a role in maintaining the normal phenotype of epithelial cells. Decreased expression of E-cadherin has been correlated with increased invasiveness of breast cancer. In other systems, inappropriate expression of a nonepithelial cadherin, such as N-cadherin, by an epithelial cell has been shown to downregulate E-cadherin expression and to contribute to a scattered phenotype. In this study, we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
647
10
13

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 700 publications
(729 citation statements)
references
References 57 publications
47
647
10
13
Order By: Relevance
“…Our finding that P-cadherin as a critical mediator of the invasive phenotype further supports the view that the incorrect expression of another adhesion molecule, rather than a decrease in E-cadherin, is associated with an increased invasive potential (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). Unlike E-cadherin, P-cadherin can promote motility and invasion in carcinoma cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our finding that P-cadherin as a critical mediator of the invasive phenotype further supports the view that the incorrect expression of another adhesion molecule, rather than a decrease in E-cadherin, is associated with an increased invasive potential (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). Unlike E-cadherin, P-cadherin can promote motility and invasion in carcinoma cells.…”
Section: Discussionsupporting
confidence: 84%
“…Instead, GnRHa stimulated activation of the P-cadherin promoter (Figure 2b; Po0.05), suggesting a transcriptional mechanism of regulation. P-cadherin contributes to the invasive phenotype It has been suggested that expression of an inappropriate cadherin may directly contribute to the invasive phenotype (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). To test whether P-cadherin may promote migration/invasion, we stably transfected Caov-3 and OVCAR-3 cells with P-cadherin and analyzed their effects on cell migration/invasion.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to study changes in the expression and localization of CRB3 (apical) and occludin (basolateral) as epithelial markers of EMT-associated processes, rather than the direct effect of E2 on the expression of these proteins. On the other hand, gradual increases of N-cadherin expression in these breast cancer cell lines were related to EMT-associated mechanisms, regardless of the E-cadherin expression [46], and could be used as stage markers during invasion processes. Furthermore, it has been reported that Ncadherin expression correlates with invasion and motility, plays a direct role in promoting motility, and is involved in EMT and cancer cell metastasis [47].…”
Section: Discussionmentioning
confidence: 96%
“…N-cadhein is upregulated in highly invasive breast cancer cell lines that lack Ecadherin expression. 39 Further, exogenous expression of N-cadherin in breast cancer cells enhances motile, invasive and metastatic ability. 40 Human squamous carcinoma cells that express N-cadherin along with a decreased expression of E-and P-cadherin disrupt cell-cell adhesion and induce a scattered fibroblastic phenotype.…”
Section: Matrix-degradative Property Of the Hoxd3 Transfectantmentioning
confidence: 99%